(untitled) (Journal of Hama University, 2024)
Aim: Comparison of durability, adhesive failure rates, refraction resistance, plaque index, gingivitis, and patient acceptance of metal cad cam retainers and those made of fiber with traditional lingual retainer Material and Methods: 42 patients (14 patients per group) were selected and apply retainers (metal and fiber) made with cad cam were as study groups and traditional wire retainers as a control group. The brackets were protected with wax, then the alginate print was taken and sent to the laboratory, where he cast it and scanned it on the scanner, then made a design of the retainer with a height of 3.5 mm and a thickness of 1 mm, then milled, and then it was affixed to the lingual surfaces of the lower incisors using double-curing cement, and we studied the variables (durability rates of adhesive failure, refraction resistance, plaque index, gingivitis, and patient acceptability) per month over a 6-month period. Results: The results of this study showed that the rates of adhesion failure were lower when using cad cam retainers. It also showed that the metal cad cam retainer was better in terms of fracture resistance. The use of cad cam retainers also improved oral health when studying the indicator of bacterial plaque and gingivitis. There was no significant difference in patients’ acceptance between the cad cam fixators and the traditional wire fixators. Conclusions: This clinical trial demonstrated the effectiveness of metal and fiber retainers manufactured using CAD CAM as a means of securing long-term fixation of mandibular incisors.